A model of blood supply to the brain via the carotid arteries: Effects of obstructive vs. sclerotic changes. (November 2017) - Onaizah, O.; Poepping, T.L.; Zamir, M.
Highlights: A model of blood flow to the brain via the carotid arteries is studied theoretically and experimentally. Effects of carotid stenosis (obstructive disease) and of local and downstream stiffening (sclerotic disease) were examined. Such local pathologies do not translate directly to effects on blood supply to the brain. Internal carotid artery flow was significantly reduced only above 70% stenosis. Vascular stiffening and downstream changes altered carotid flow or flow waveform. Abstract: The carotid artery is one of the major supply routes of blood to the brain and a common site of vascular disease. Obstructive and sclerotic disorders within the carotid artery impact local blood flow patterns as well as overall impedance and blood supply to the brain. A lumped parameter model and an experimental in-vitro flow loop were used to study the effects of local stenosis and stiffness in the carotid artery based on a family of phantoms with different degrees of stenosis and compliance. The model also allows independent examination of the effects of downstream resistance and compliance. Mild to moderate stenosis was found to lead to minimal (∼1%) reduction in blood supply to the brain. Reduction in mean internal carotid artery (ICA) flow was statistically significant ( p < 0.01) only above 70% stenosis. On the other hand, a three-fold increase in stiffness of the carotid artery, as might occur in aging, was found to lead to a modest yet statistically significant reduction ( p < 0.01) in mean ICA flow. Effects of changing downstream resistance and compliance were examined. For a given pressure waveform, reduction in downstream compliance led to altered waveform shape and reduction in peak systolic flow rates where the mean flow rates were not altered. Increased downstream resistance resulted in drastic reduction in mean flow rates.